2012
DOI: 10.1097/mao.0b013e318259b38c
|View full text |Cite
|
Sign up to set email alerts
|

Otosclerosis

Abstract: CBCT is a new imaging technique with a considerably lower radiation dose than conventional MSCT. Our study indicates that CBCT is suitable and, in many ways, equivalent to MSCT, for temporal bone imaging in otosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In another study, two types of heterotopic mineralization (ossification, including abaxial avulsion fracture of the proximal sesamoid bones, and ligament and tendon mineralization) were reliably detected using CBCT imaging of the equine fetlock region ( 25 ). Likewise, the general suitability of CBCT imaging for the diagnostic assessment of bony structures and bone-related pathologies has been shown by numerous comparative studies on human skeletal structures ( 29 , 30 ). Using clinically applied protocols, both CBCT and MDCT imaging produced diagnostic images for the assessment of the human pelvis, head, and neck.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, two types of heterotopic mineralization (ossification, including abaxial avulsion fracture of the proximal sesamoid bones, and ligament and tendon mineralization) were reliably detected using CBCT imaging of the equine fetlock region ( 25 ). Likewise, the general suitability of CBCT imaging for the diagnostic assessment of bony structures and bone-related pathologies has been shown by numerous comparative studies on human skeletal structures ( 29 , 30 ). Using clinically applied protocols, both CBCT and MDCT imaging produced diagnostic images for the assessment of the human pelvis, head, and neck.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, CBCT showed a sensitivity of 100% in cases of active otosclerosis but dropped to 0% in cases of inactive otosclerosis [ 20 ]. Another study by Redfors et al found that HRCT had higher sensitivity than CBCT, specifically for fenestral otosclerotic lesions [ 21 ]. The U-HRCT device in this study is designed based on the principle of CBCT, and the acquisition layer thickness was 0.1 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was found in several studies that the invasion of the cochlear endoste by the otosclerotic foci on CT is correlated with a poor prognosis [4] [10] [16] [17]. Indeed, this phenomenon leads to a release of enzymes in the labyrinthine fluid, causing inflammation and degeneration of intra-cochlear structures, which can lead to severe sensorineural hearing loss [4] [18]- [20].…”
Section: Discussionmentioning
confidence: 99%